Estudo do comportamento à fadiga de misturas asfálticas aplicadas em campo por meio da teoria viscoelástica de dano contínuo - Schuster, Silvio Lisboa (2018)
The behaviour analisys of asphalt mixtures is extremely important in the paving cenarium, whose final objective is to improve the performance combined with resources saving. It is known that the fatigue cracking is the main type of defect in asphalt roads. In this way, the study proposes evaluate twenty-four asphalt mixtures used in the field, aiming to understand how their different characteristics influence the fatigue resistance. The laboratory tests are the main resource for the study of the phenomenon of fatigue in asphalt mixtures. This work is based on the Direct Tension Cyclic Fatigue test and, through the data obtained, it proposes to apply the Simplified Viscoelastic Continumm Damage model (S-VECD). The data obtained from the S-VECD model, with the viscoelastic properties presented by Faccin (2018) (for the same mixtures) served as a basis for the application of the FlexPAVE - Layered Viscoelastic Pavement Analysis for Critical Distresses software. In this way, it was possible to evaluate the accumulated damage over time and to analyze the performance of the pavement, classifying the mixtures considering fatigue damage. It was possible to verify the strong influence of the type of binder on the levels of accumulated fatigue damage, which mixtures with modified binder by polymer and by rubber present better results than mixtures with conventional binder. Despite the large number of intrinsic variables of mixtures, it was also possible to observe evidences of correlations between fatigue damage and characteristics, such as composition granulometry, shape and texture of aggregates and binder content. The fatigue strength was correlated with the rutting resistance obtained by Faccin (2018), thus being able to fully classify the mixtures according two main types of defects of the asphalt roads. Correlations between the damage and linear viscoelastic characterization were tested and proved to be poorly effective in predicting fatigue damage from stiffness behavior. The study also applied classical approaches to fatigue by constructing the Wöhler curves with the experimental data, demonstrating that this approach should be applied with caution, since it does not have much representation with the evaluation of the damage, considering simulations under field conditions. In general, for the asphalt concretes used in Rio Grande do Sul presented low and medium damage levels in relation to the fatigue phenomenon.